THE EFFECT OF CAREER DEVELOPMENT ON EMPLOYEE SATISFACTION AT PT CHAROEN POKPHAND INDONESIA - Gres Nelda Salu Randan (The Scientia Law and Economics Review, 2023)
The Effect of Career Development on Employee Job Satisfaction at PT Charoen Pokphand Indonesia in Makassar class of 2018. This study aims to determine career development has a significant effect on employee job satisfaction at PT Charoen Pokphand Indonesia. the type of data in this study is quantitative data using pearson product moment correlation analysis, the coefficient of determination and the t test. while the data sources are primary data and secondary data. Interview and questionnaire data collection methods sent a Google Form survey to 143 employees of PT Chaeron Pokphand Indonesia in Makassar. Based on the research results, the correlation coefficient (r) was obtained = 0.707, the coefficient of determination (r²) = 50%, t count = 7.540 > t table = 1.672. This means that career development has a significant effect on employee job satisfaction at PT Charoen Pokphand Indonesia in Makassar.